Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/all.12407
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐155 controls mast cell activation by regulating the PI3Kγ pathway and anaphylaxis in a mouse model

Abstract: Thus, we suggest that miR-155 plays a critical role in FcεRI-mediated MC responses by modulating components of the PI3Kγ pathway. This newly identified mechanism of miRNA-controlled MC activation may affect the initiation and maintenance of allergic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 34 publications
0
48
1
Order By: Relevance
“…Additionally, an increasing number of studies have identified altered miRNA expression in diverse immune responses and immunologic disorders [25][26][27][28][29][30][31][32][33]. In contrast, the expression and function of specific miRNAs during the differentiation, proliferation and activation of mast cells has received little attention [34][35][36][37][38][39][40][41]. Mayoral et al [37] reported that miR-221-222 were detectably up-regulated in BMMC stimulated for 1 h or 24 h with PMA and ionomycin, and regulated cell cycle checkpoints in mast cells in response to acute stimulation, Only individual miRNAs have been implicated in mast cell degranulation and cytokine production because of their role in the post-transcriptional fine-tuning mechanisms of gene expression, which are associated with the FcεRI signaling pathway [35,36,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an increasing number of studies have identified altered miRNA expression in diverse immune responses and immunologic disorders [25][26][27][28][29][30][31][32][33]. In contrast, the expression and function of specific miRNAs during the differentiation, proliferation and activation of mast cells has received little attention [34][35][36][37][38][39][40][41]. Mayoral et al [37] reported that miR-221-222 were detectably up-regulated in BMMC stimulated for 1 h or 24 h with PMA and ionomycin, and regulated cell cycle checkpoints in mast cells in response to acute stimulation, Only individual miRNAs have been implicated in mast cell degranulation and cytokine production because of their role in the post-transcriptional fine-tuning mechanisms of gene expression, which are associated with the FcεRI signaling pathway [35,36,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…PIK3R6 is a phosphoinositide 3-kinase (PI3K)γ subunit (32). PI3Ks are classified as class I, II or III based on substrate binding and sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell degranulation and cytokine production are inhibited by both miR-155 and miR-223 and correlate with selective alterations in PI3K-AKT pathway activity, though the direct mRNA targets remain to be identified [39,40]. Degranulation and adherence in response to FcεR ligation are enhanced by both miR-142-3p and miR-221.…”
Section: Mirnas Participate In Gene Network That Regulate Signaling mentioning
confidence: 99%
“…miR-155 −/− mice have reduce airway hypersensitivity and increased passive cutaneous anaphylaxis responses [39,47]. T cell-intrinsic expression of miR-155 promotes airway hyperresponsiveness (AHR) in asthma models, in part through the regulation of the direct target S1pr1 and recruitment of effector cells to the lung [47,48].…”
Section: Mirna In the Treatment Of Allergic Diseasementioning
confidence: 99%